Ecological distribution of protosteloid amoebae in New Zealand - Geoffrey Zahn; Steven L. Stephenson; Frederick W. Spiegel (PeerJ, 2014)
During the period of March 2004 to December 2007, samples of aerial litter (dead but still attached plant parts) and ground litter (dead plant material on the ground) were collected from 81 study sites representing a wide range of latitudes (34°S to 50°S) and a variety of different types of habitats throughout New Zealand (including Stewart Island and the Auckland Islands). The objective was to survey the assemblages of protosteloid amoebae present in this region of the world. Twenty-nine described species of protosteloid amoebae were recorded by making morphological identifications of protosteloid amoebae fruiting bodies on cultured substrates. Of the species observed, Protostelium mycophaga was by far the most abundant and was found in more than half of all samples. Most species were found in fewer than 10% of the samples collected. Seven abundant or common species were found to display significantly increased likelihood for detection in aerial litter or ground litter microhabitats. There was some evidence of a general correlation between environmental factors - annual precipitation, elevation, and distance from the equator (latitude) - and the abundance and richness of protosteloid amoebae. An increase in each of these three factors correlated with a decrease in both abundance and richness. This study provides a thorough survey of the protosteloid amoebae present in New Zealand and adds to a growing body of evidence which suggests several correlations between their broad distributional patterns and environmental factors.